Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/conl.12678
|View full text |Cite
|
Sign up to set email alerts
|

Natural history films raise species awareness—A big data approach

Abstract: In urbanized societies that are increasingly disconnected from nature, communicating ecological and species awareness is crucial to revert the global environmental crisis. However, our understanding of the effectiveness of this process is limited. We present a framework for describing how such awareness may be transferred and test it on the popular BBC show Planet Earth 2 by analyzing Twitter and Wikipedia big data activity. Despite lacking explicit conservation themes, this show generated species awareness, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 32 publications
(40 reference statements)
0
52
1
Order By: Relevance
“…For example, Nolan (2010) found that despite the documentary An Inconvenient Truth increasing viewer's concerns about global climate change, this did not lead to a sustained adoption of behaviors to reduce greenhouse gas emissions. Similarly, the nature documentary series Planet Earth 2 was found to increase species awareness and stimulate engagement among audiences, however this was not found to lead to proactive actions such as donation behaviors (Fernández‐Bellon & Kane, 2019). Both studies also highlight that awareness means very little in the context of behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nolan (2010) found that despite the documentary An Inconvenient Truth increasing viewer's concerns about global climate change, this did not lead to a sustained adoption of behaviors to reduce greenhouse gas emissions. Similarly, the nature documentary series Planet Earth 2 was found to increase species awareness and stimulate engagement among audiences, however this was not found to lead to proactive actions such as donation behaviors (Fernández‐Bellon & Kane, 2019). Both studies also highlight that awareness means very little in the context of behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Although we detected an increase in Wikipedia visits in early 2017, this is unlikely to have depended upon a lagged effect of the blacklist. Usually, news exposure boosts people's interest towards a certain topic in the short term, and the number of on-line searches progressively declines through time [30] [31] . Therefore, we would have expected an increase in Wikipedia views soon after the publication of the blacklist, in August 2016, and not 6 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that success of natural history documentaries has raised awareness for many exotic species and led to vicarious connections and public engagement on par with targeted conservation campaigns (Fernández‐Bellon & Kane, 2019). An ABM allows students to select any case‐study species regardless of location and formulate hypotheses of their own choosing without a fieldwork component.…”
Section: Why Use An Agent‐based Model?mentioning
confidence: 99%
“…travel to exotic locations to complete fieldwork for their undergraduate or masters thesis if funding is unavailable. Research has shown that success of natural history documentaries has raised awareness for many exotic species and led to vicarious connections and public engagement on par with targeted conservation campaigns(Fernández-Bellon & Kane, 2019). An ABM allows students to select any case-study species regardless of lo-…”
mentioning
confidence: 99%